A Clinical Study of Haritaki Mixed with Gavya Ghrita in Vibandha with special reference to Samyoga Guna - Hansdah, Monalisa; Das, Arun Kumar; Sahoo, Manoj Kumar; Behera, Shibabrata (International Research Journal of Ayurveda & Yoga, 2022)
In Ayurveda, every fundamental principle has its own practical utility and most of the concepts are expressed with Gunas. In Ayurveda Gunas described have been divided into various categories like Adhyatmika Gunas, Gurvadi gunas, Paradi gunas, Visista(Artha) Gunas etc. Among these Gunas, for the success and accomplishment of treatment, Paradi guna are the most important factor. These properties are very much useful in pharmaceutics, researches and clinics. So there is a large scope for application of Paradi gunas in field of research. These are total ten in in number and enlisted in a way which begin in clinical practice or medical field, In clinical practice Guna which are to be with Bhisak are mainly the Paradi Gunas which can also be called miscellaneous Gunas. As rightly quoted by Acharya Charaka, for getting success in the treatment Paradi gunas are the best. The sutra quotes “Sidhyupaya chikischayam” which means that chikitsa i.e Dhatusamya will be done mainly with the help of paradi gunas. In paradi Guna Samyoga Guna one of them. Samyoga is a property which has been used by physicians and pharmacists in formulating different yogas and on the basis of this property; it is decided which substances are to be combined or mixed with other substances. Thus in this study an attempt was made to know the comparative effect of Haritaki churna and Haritaki churna mixed Gavya Ghrita Samyukta effect in vibandha.